Algunas consideraciones con miras al fortalecimiento del sistema de inspección del trabajo peruano - De Lama Laura, Manuel Gonzalo (2023)
In this article, the author analyzes and proposes some alternatives with a view to strengthening the Peruvian labor inspection system. In this way, he discusses the exclusion of the inspection procedure from the application of the rules of the general administrative procedure, reviews some criteria of the Committee of the National Superintendence of Labor Inspection-SUNAFIL and, finally, analyzes the non-suspension of the inspection procedure in the case of a related judicial process.